On a Possibility of Increase of Efficiency of Communications of National Diasporas of St. Petersburg - Akhverdy Chobanogly Imanov; Valery Vitalyevich Yanovskiy (Управленческое консультирование, 2018)
In connection with the need to develop national and cultural communities and the formation of such conditions that will preserve national dignity and self-awareness on the basis of the national consolidation of the peoples of Russia, efforts to maintain the spirit of interethnic communication in St. Petersburg are needed. Communication, which does not conflict with national self-identification are needed. This will not only avoid inter-ethnic tensions, conflicts between nations, but also eliminate the risks of confrontation with the structures of power and government. To this end, we are proposing to implement in St. Petersburg and Leningrad Region a single project «House of Nationalities».